2020
DOI: 10.1108/mrr-02-2020-0068
|View full text |Cite
|
Sign up to set email alerts
|

The effects of IT use intensity and innovation culture on organizational performance: the mediating role of innovation intensity

Abstract: Purpose This study aims to investigate innovation intensity by exploring the roles of internally focused and externally focused information technology (IT) use intensity and innovation culture on innovation intensity and organizational performance. Design/methodology/approach A model exploring the effects of internally and externally focused IT use, plus two key dimensions of innovation culture – collaborative and entrepreneurial – on innovation intensity and organizational performance is tested via a struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…The Competing Value Framework (CVF) Model by Cameron and Quinn (1999);Schein's Model (1990); Rao and Weintraub (2013); Hoogan and Coote's (2014); Dobni's (2018) are among the widely used organisational culture theories used to study innovation culture in an educational context (Fuad et al, 2020). As a result, it is difficult to measure innovation culture because of its broad extent and the lack in its operationalisation (Bourdeau et al, 2020). However, research conducted in recent years demonstrated a consistent trend across all of them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Competing Value Framework (CVF) Model by Cameron and Quinn (1999);Schein's Model (1990); Rao and Weintraub (2013); Hoogan and Coote's (2014); Dobni's (2018) are among the widely used organisational culture theories used to study innovation culture in an educational context (Fuad et al, 2020). As a result, it is difficult to measure innovation culture because of its broad extent and the lack in its operationalisation (Bourdeau et al, 2020). However, research conducted in recent years demonstrated a consistent trend across all of them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Innovation in the IT industry in the context of organizational culture has attracted much attention recently (Abubakre et al, 2020;Bourdeau et al, 2020;Fan et al, 2019;Nguyen et al, 2019). However, none of the studies has considered the culture of knowledge or learning in the context of tacit knowledge.…”
Section: Conceptual Frameworkmentioning
confidence: 99%